2014
DOI: 10.1002/ejoc.201402751
|View full text |Cite
|
Sign up to set email alerts
|

Iron(III)‐Catalyzed C–H Functionalization: ortho‐Benzoyloxylation of N,N‐Dialkylanilines and Its Application to 1,4‐Benzoxazepines

Abstract: A C–O bond‐formation reaction that proceeds through C–H functionalization of N,N‐dialkylanilines at the ortho‐position is presented. The iron‐catalyzed selective ortho‐benzoyloxylation follows a polar Friedel–Crafts‐like mechanism and is sensitive to the nucleophilicity of the anilines. The benzoyloxylation of a variety of N,N‐disubstituted anilines and N‐phenyl heterocycles is carried out under extremely mild conditions. Furthermore, the methodology has been successfully employed for the generation of 1,4‐ben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…Over the years, methods for mediating the oxidative coupling between tertiary or secondary aniline derivatives and phenols have been reported. Chandrasekharam 6 and Knolker 7 developed conditions for the iron-catalyzed oxidative cross-coupling between N , N -dialkylanilines and 2-naphthols, and Shindo reported that a heterogeneous Rh–C catalyst mediates the oxidative coupling between 1-(2-naphthalenyl)piperidine and phenol derivatives ( Scheme 1 A). 8 The accepted mechanism underlying these reactions, which affords the N , O -biaryl products, involves the coupling between the tertiary anilino radical and nucleophilic phenol(ate).…”
mentioning
confidence: 99%
“…Over the years, methods for mediating the oxidative coupling between tertiary or secondary aniline derivatives and phenols have been reported. Chandrasekharam 6 and Knolker 7 developed conditions for the iron-catalyzed oxidative cross-coupling between N , N -dialkylanilines and 2-naphthols, and Shindo reported that a heterogeneous Rh–C catalyst mediates the oxidative coupling between 1-(2-naphthalenyl)piperidine and phenol derivatives ( Scheme 1 A). 8 The accepted mechanism underlying these reactions, which affords the N , O -biaryl products, involves the coupling between the tertiary anilino radical and nucleophilic phenol(ate).…”
mentioning
confidence: 99%
“…A milder procedure 21 with 3 M sulfuric acid rather than concentrated acid, formaldehyde, and sodium borohydride provided a mixture of the starting material, monomethylated substrate, and the desired dimethylamine. Additionally, reductive amination with sodium cyanoborohydride, paraformaldehyde, and glacial acetic acid, adapted from the literature, 22 produced significant amounts of side products.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The preparation of the dimethylamines was described according to Escheweiler–Clarke conditions. , The ammonium triflates were prepared according to the literature . To a solution of 4-methoxyaniline (1.2 g, 10.0 mmol, 1.0 equiv) in MeOH (15 mL) under Ar was added formic acid to adjust the pH to 3–4.…”
Section: Methodsmentioning
confidence: 99%